Book of Abstracts 2017
DOI: 10.18690/978-961-286-045-5.2
|View full text |Cite
|
Sign up to set email alerts
|

Specifics of vegetable production for processing

Abstract: Layout:Tjaša Vukmanič and Urška Lisec

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Mineral fertilization resulted in twice the yield compared to organic fertilization (Tables 1 and 1a). The obtained results are in accordance with previous research by authors Lešić et al (2016) and Matotan (2004), who states an average yield of 15 to 30 t/ha, depending on whether it was spring or autumn cultivation. Also, Canali et al (2014) have revealed the average yield from 38.8 to 40.7 t/ha, depending on the year of cultivation, and from 31.2 to 46.6 t/ha, depending on the amount of added nitrogen.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Mineral fertilization resulted in twice the yield compared to organic fertilization (Tables 1 and 1a). The obtained results are in accordance with previous research by authors Lešić et al (2016) and Matotan (2004), who states an average yield of 15 to 30 t/ha, depending on whether it was spring or autumn cultivation. Also, Canali et al (2014) have revealed the average yield from 38.8 to 40.7 t/ha, depending on the year of cultivation, and from 31.2 to 46.6 t/ha, depending on the amount of added nitrogen.…”
Section: Resultssupporting
confidence: 93%
“…and Correll J.C, 2008). The root system grows rapidly, and the main root reaches the length of up to 180 cm, on which numerous lateral roots develop, most often in the arable layer, 15-30 cm deep, whose diameter corresponds to the diameter of the rosette (Matotan, 2004). In the vegetative phase, the spinach stem is short, overgrown with a rosette of leaves on longer and shorter petioles.…”
Section: Introductionmentioning
confidence: 99%
“…Newly arrived vegetables have been called "paradiesapfel" in Germany, which means paradise apple. The current scientific name for the Lycopersicon esculentum tomato was suggested by the English botanist Miller in 1768, which would translate into a wolf's edible apple (Matotan, 2008). Tomatoes for eating in Europe are thought to be first used in Italy in the mid-sixteenth century, and then spread to other Mediterranean countries and later to northern Europe.…”
Section: Introductionmentioning
confidence: 99%